Study of mesh pattern for optically transparent flexible antenna with feedline - Yu, Seulgi; Lee, Soyeong; Lee, Hoosung; Park, Yong Bae (Applied Sciences (Switzerland), 2021)
This paper presents a systematic parameter study on mesh pattern for optically transparent flexible antenna with feedline. In implementing a transparent flexible antenna using a metal mesh, transparency and performance of antenna and feedline are opposite factors. To understand how both elements are affected by the design parameters of the mesh, we analyze the performance of the feedlines and antennas according to the design parameters of diamond and square meshes. Moreover, the effect of the difference in the shape of diamond mesh and square mesh on performance is analyzed. The measured results of the fabricated samples offer the feasibility of implementing transparent feedlines and antennas with similar performance to nontransparent feedlines and antennas.
Keywords: Diamond-grid; Flexible antennas; Meshed antennas; Metal mesh film; Monopole antennas; Transparent antennas